Pediatric hypertrophic cardiomyopathy caused by a novel TNNI3 variant - Natsuko Inagaki; Tomoya Okano; Masatake Kobayashi; Masatsune Fujii; Yoshinao Yazaki; Yasuyoshi Takei; Hisanori Kosuge; Shinji Suzuki; Takeharu Hayashi; Masahiko Kuroda; Kazuhiro Satomi (Human Genome Variation)
Abstract TNNI3 is a gene that causes hypertrophic cardiomyopathy (HCM). A 14-year-old girl who was diagnosed with nonobstructive HCM presented with cardiopulmonary arrest due to ventricular fibrillation. Genetic testing revealed a novel de novo heterozygous missense variant in TNNI3, NM_000363.5:c.583A>T (p.Ile195Phe), which was determined to be the pathogenic variant. The patient exhibited progressive myocardial fibrosis, left ventricular remodeling, and life-threatening arrhythmias. Genetic testing within families is useful for risk stratification in pediatric HCM patients.